Methodology and organization of scientific research in the field of biology - Sukhomlin, Kateryna B.; Zinchenko, Oleksandr P.; Sukhomlyn, Maryna M.; Zinchenko, Mariia O. (Lesya Ukrainka Volyn National University, 2023)
The publication contains methodical instructions for the implementation of 6 practical works in the course «Methodology and organization of scientific research in the field of biology», provided by the curriculum of the Master's degree program in specialty 091 «Biology and Biochemistry» for foreign students. The papers cover the theoretical foundations of the methodology, technology and organization of research activities, i.e. the theoretical and practical basis for the effective conduct of research by undergraduates. Each laboratory work contains a theme, goal, questions for knowledge control, progress of the work, and a list of references.
Keywords: science; research; methods; 001.89(075.8)